Death in Contemporary Popular Culture - Teodorescu, Adriana; Jacobsen, Michael Hviid, 1971- (Milton : Routledge, 2019)
With intense and violent portrayals of death becoming ever more common on television and in cinema and the growth of death-centric movies, series, texts, songs, and video clips attracting a wide and enthusiastic global reception, we might well ask whether death has ceased to be a taboo. What makes thanatic themes so desirable in popular culture? Do representations of the macabre and gore perpetuate or sublimate violent desires? Has contemporary popular culture removed our unease with death? Can social media help us cope with our mortality, or can music and art present death as an aesthetic phenomenon? This volume adopts an interdisciplinary approach to the discussion of the social, cultural, aesthetic, and theoretical aspects of the ways in which popular culture understands, represents, and manages death, bringing together contributions from around the world focused on television, cinema, popular literature, social media and the internet, art, music, and advertising.
11 Death in Don DeLillo's White Noise: A literary diagnosis of contemporary death culture12 Narratives of death and immortality in the 'Islamic State' discourse on Twitter; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General; Death in popular culture